Pengaruh Work Stres Dan Self Control Terhadap Cyberloafing Pada Pegawai Di Badan Penghubung Provinsi Sulawesi Barat - Aqil, Muhammad; Dahri, Nur Wahyunianti; Barung, Rachmat; Abdullah, M Said; Nurmiati (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
The aim of this research is to determine the influence of work stress and self-control on cyberloafing among employees at the West Sulawesi Provincial Liaison Agency. This research uses quantitative methods by collecting data through questionnaires. This research was carried out at the West Sulawesi Provincial Liaison Agency with a sample size of 50 people. Questionnaire data were analyzed with the help of the SPSS program. The results of the research show that the t¬calculated work stress value of 2.730 is greater than the t-table 2.012 and the significance value of 0.009 is smaller than 0.05 so that work stress has a partially significant effect on cyberloafing among employees at the West Sulawesi Provincial Liaison Agency, self-t¬counted value control of 2.339 is greater than t table 2.012 and the significance value of 0.024 is smaller than 0.05 so that self control has a partially significant effect on cyberloafing in employees at the West Sulawesi Provincial Liaison Agency then work stress and self control have a value of F count of 7.240 which is greater than F table 3 .19 and the significance value of 0.002 is smaller than 0.05 so that work stress and self control have a significant simultaneous effect on cyberloafing among employees at the West Sulawesi Provincial Liaison Agency